THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION, GOVERNMENT SUPPORT AND SOCIAL MEDIA ADOPTION ON THE PERFORMANCE OF SMES: A VOLATILE ENVIRONMENT PERSPECTIVE - Md Saad, Norsafinas; Datu Bandira, Puteri Nurul Nazuha; Ahmad-Fauzi, Nur Rosdiatul Husna (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Small and Medium Enterprises (SMEs) have a notable impact on global economies, including Malaysia, by contributing substantially to the nation’s exports, income growth, and job creation. Their strategic role is particularly crucial for improving economic conditions, especially in rural economies like Perlis. However, the emergence of outbreaks and environmental turbulence created uncertainty in the market and disrupted economies on a global scale. Even in Perlis, Malaysia’s smallest and northernmost state, SMEs have faced difficulties during these volatile times. These enterprises have encountered various difficulties in maintaining their business survival. As a response to these challenges, this study is set forth to investigate the key factors that can help SMEs to sustain firm performance during challenging business environments. It investigates three entrepreneurial orientation (EO) dimensions - proactiveness, innovativeness, and risk-taking - along with government support, and social media adoption as the independent variables, with SMEs’ business performance as the dependent variable. The data was gathered through questionnaires, involving the total participation of 129 SMEs in Perlis. The findings revealed that risk-taking, government support, and social media adoption are significant predictors of SMEs’ business performance, while SMEs’ proactiveness and innovativeness showed no significant effect on the performance of SMEs in Perlis. These findings hold important implications for SMEs, highlighting the need to embrace calculated risks, foster good relationships with government agencies, and leverage social media to enhance their market position, especially in volatile conditions. Policymakers could use these inputs to develop strategies, policies and support mechanisms tailored to SMEs facing uncertain market and economic challenges.